The Measurement of the Current Portion of the Long-Term Lease Obligations–Some Evidence from Practice. - Stickney, Clyde P.; Richardson, A. W. (The Accounting Review, 1985)
Abstract ABSTRACT: There are currently no definitive guidelines for reporting the current and noncurrent portions of lease obligations. Two possible approaches to this problem of allocation-the change in present value approach and the present value of the next year's payments approach–have been identified by Swieringa [1984]. This article addresses two aspects of this financial reporting issue. First, evidence is presented to show that the change in present value approach appears to be dominant in current financial reporting practice. Second, it is shown that adjustment of the reported financial statement numbers to those that would be obtained by the present value of the next year's payments approach does not affect the ranking of companies by a number of financial measures. These results suggest that the issuing of guidelines for reporting the current and noncurrent portions of lease obligations by the FASB is not warranted.